Positive electrode active material, manufacturing method for the same, positive electrode including the same, and lithium secondary battery
Patent Information
- Application Number
- JP2024128611
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-03
- Filing Date
- 2024-08-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-08-05
AI Technical Summary
【0009】 本発明の一実施形態による正極活物質は、生産価格を最小化し、かつ、容量を極大化したもので、長寿命特性が確保され、高電圧での特性および高温特性が改善される。前記正極活物質を適用したリチウム二次電池は、高電圧条件でも高い初期充放電容量および効率を示すことができ、長寿命特性を実現することができ、高電圧および高温駆動によるガス発生問題を効果的に抑制することができる。
Smart Images

Figure 2025022870000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material, a method for producing the same, a positive electrode containing the same, and a lithium secondary battery. [Background technology]
[0002] Lithium secondary batteries, which have high energy density and are easy to carry, are mainly used as the driving power source for mobile information terminals such as mobile phones, laptops, and smartphones. Recently, active research has been conducted on using high-energy-density lithium secondary batteries as driving power sources or power storage sources for hybrid and electric vehicles.
[0003] In order to realize lithium secondary batteries that meet these applications, various positive electrode active materials have been studied. Among them, lithium nickel oxide, lithium nickel manganese cobalt composite oxide, lithium nickel cobalt aluminum composite oxide, lithium cobalt oxide, etc. are mainly used as positive electrode active materials. However, in recent years, while the demand for large-sized, high-capacity, or high-energy density lithium secondary batteries has rapidly increased, the supply of positive electrode active materials containing the rare metal cobalt is expected to be extremely short. In other words, since cobalt is expensive and there are not many remaining reserves, it is necessary to develop positive electrode active materials that do not contain cobalt or have a reduced cobalt content. Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention provides a positive electrode active material containing a lithium nickel-manganese composite oxide, which is economical, has high capacity, and has long life characteristics, and has improved high voltage characteristics and high temperature characteristics, a method for producing the same, and a positive electrode and a lithium secondary battery containing the same. [Means for solving the problem]
[0005] In one embodiment of the present invention, a positive electrode active material is provided, which includes core particles containing a lithium nickel-manganese based composite oxide in which the nickel content is 60 mol % or more relative to 100 mol % of all metals excluding lithium, and a coating layer located on the surface of the core particles and containing Al, Zr, and Mg.
[0006] In another embodiment of the present invention, there is provided a method for producing a positive electrode active material, comprising: (i) mixing a nickel-manganese-based composite hydroxide having a nickel content of 60 mol % or more relative to 100 mol % of all metals and a lithium raw material, and performing a first heat treatment to obtain a lithium nickel-manganese-based composite oxide; (ii) introducing the obtained lithium nickel-manganese-based composite oxide into a solution in which an Al raw material is mixed in an aqueous solvent, mixing, and then drying; and (iii) dry-mixing the obtained product with a Zr raw material and an Mg raw material, and performing a second heat treatment to obtain a positive electrode active material.
[0007] In another embodiment of the present invention, a positive electrode is provided that includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material described above.
[0008] In another embodiment of the present invention, there is provided a lithium secondary battery comprising the positive electrode, the negative electrode, and an electrolyte. Effect of the Invention
[0009] The positive electrode active material according to an embodiment of the present invention minimizes production costs and maximizes capacity, while ensuring long life characteristics and improving high voltage and high temperature characteristics. A lithium secondary battery using the positive electrode active material can exhibit high initial charge / discharge capacity and efficiency even under high voltage conditions, realize long life characteristics, and effectively suppress gas generation problems caused by high voltage and high temperature operation. [Brief description of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention is not limited to the embodiments described herein, but may be embodied in various different forms.
[0012] The terms used herein are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless otherwise clearly indicated in the context.
[0013] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of compositions.
[0014] It should be understood that the terms "including," "comprising," or "having" are intended to specify the presence of embodied features, numerals, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numerals, steps, components, or combinations thereof.
[0015] In the drawings, the thickness of the various layers and regions is exaggerated for clarity, and similar parts are designated by the same reference numerals throughout the specification. When a part such as a layer, film, region, plate, etc. is said to be "on" or "on" another part, this includes not only the case where it is "directly on" the other part, but also the case where there is another part between them. Conversely, when a part is said to be "directly on" another part, it means that there is no other part between them.
[0016] Further, the term "layer" as used herein includes not only a shape formed on the entire surface when observed in a plan view, but also a shape formed on a portion of the surface.
[0017] The average particle size can be measured by a method well known to those skilled in the art, for example, by using a particle size analyzer or by using a transmission electron microscope image or a scanning electron microscope image. Alternatively, the average particle size can be obtained by measuring using a dynamic light scattering method, counting the number of particles for each particle size range by performing data analysis, and then calculating the average particle size value. Unless otherwise defined, the average particle size means the diameter (D50) of particles whose cumulative volume is 50% by volume in the particle size distribution. In addition, unless otherwise defined, the average particle size can be obtained by measuring the size (diameter or major axis length) of 20 or more particles randomly from a scanning electron microscope image to obtain a particle size distribution, and taking the diameter (D50) of particles whose cumulative volume is 50% by volume in the particle size distribution as the average particle size.
[0018] As used herein, "or" is not to be construed in an exclusive sense, e.g., "A or B" is to be construed as including A, B, A+B, etc.
[0019] The term "metal" is interpreted as including general metals, transition metals, and metalloids (semimetals).
[0020] positive electrode active material In one embodiment of the present invention, a positive electrode active material is provided, which includes core particles containing a lithium nickel-manganese based composite oxide in which the nickel content is 60 mol % or more relative to 100 mol % of all metals excluding lithium, and a coating layer located on the surface of the core particles and containing Al, Zr, and Mg.
[0021] In recent years, the price of cobalt, a rare metal, has been soaring, and there is a demand for the development of positive electrode active materials that do not contain cobalt or that have a reduced cobalt content. Among these, positive electrode active materials with an olivine crystal structure, such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), and lithium manganese iron phosphate (LMFP), or a spinel crystal structure, such as lithium manganese oxide (LMO), have a limited capacity due to the small amount of lithium that can be utilized within the structure. Layered nickel-manganese positive electrode active materials have excellent capacity and efficiency characteristics because they can increase the amount of lithium within the structure, making them suitable as materials for high-capacity batteries. However, the removal of cobalt, which plays a key role in the layered structure, reduces structural stability, increases resistance, and makes it difficult to ensure long life characteristics. In addition, the removal of cobalt accelerates side reactions between the positive electrode active material and the electrolyte under high voltage and high temperature conditions, increasing the amount of gas generated and reducing life characteristics.
[0022] In one embodiment, a layered lithium nickel manganese composite oxide is applied to core particles, and a coating layer containing Al, Zr, and Mg is introduced to provide a cathode active material that can maximize capacity and efficiency while minimizing production costs, reduce gas generation even under high voltage and high temperature conditions, and achieve long life characteristics.
[0023] Core Particles The core particle includes a lithium nickel-manganese composite oxide, and the nickel content is 60 mol% or more relative to 100 mol% of the total metals excluding lithium in the positive electrode active material. Nickel is contained in the core particle, but a part of it can move to the coating layer during the coating process, and therefore the nickel content means the nickel content contained in the entire positive electrode active material. The nickel content can be, for example, 60 mol% to 80 mol%, 65 mol% to 80 mol%, 70 mol% to 80 mol%, 60 mol% to 79 mol%, 60 mol% to 78 mol%, or 60 mol% to 75 mol% relative to 100 mol% of the total metals excluding lithium in the positive electrode active material. When the nickel content satisfies the above range, a high capacity can be achieved, and structural safety can be improved even if the cobalt content is reduced.
[0024] The manganese content is, for example, 10 mol% to 40 mol% relative to 100 mol% of all metals excluding lithium in the lithium nickel-manganese composite oxide, and can be, for example, 10 mol% to 39 mol%, 10 mol% to 35 mol%, 10 mol% to 30 mol%, 10 mol% to 29 mol%, 15 mol% to 39 mol%, 20 mol% to 39 mol%, 20 mol% to 30%, etc. When the manganese content satisfies the above range, the positive electrode active material can improve structural stability while realizing a high capacity.
[0025] The lithium nickel-manganese composite oxide may be, for example, a lithium nickel-manganese-aluminum composite oxide further containing aluminum in addition to nickel and manganese. When the composite oxide contains aluminum, it is advantageous to maintain a stable layered structure even if the cobalt element is excluded from the structure. The content of aluminum relative to 100 mol% of the lithium nickel-manganese-aluminum composite oxide may be 0.1 mol% or more, 0.5 mol% or more, or 1 mol% or more, for example, 1 mol% to 3 mol%, 1 mol% to 2.5 mol%, 1 mol% to 2 mol%, or 1 mol% to 1.9 mol%. When the content of aluminum satisfies the above range, a stable layered structure can be maintained even if cobalt is excluded, and the problem of the structure collapsing due to charging and discharging can be suppressed, and the long life characteristics of the positive electrode active material can be realized.
[0026] According to one embodiment, the aluminum concentration in the core particle may be uniform. That is, the aluminum concentration in the core particle may be uniformly distributed without having a concentration gradient from the center to the surface, or the aluminum concentration in the core particle is higher or lower than that in the inside, and the aluminum is uniformly dispersed in the core particle. This structure can be obtained by synthesizing a composite oxide using nickel-manganese-aluminum hydroxide as a precursor by using an aluminum raw material in the preparation of a precursor without further doping aluminum during the synthesis of the core particle. The core particle may be in the form of a secondary particle in which a plurality of primary particles are aggregated, and the aluminum content in the primary particle may be the same or similar regardless of the position of the primary particle. That is, when a primary particle is selected from an arbitrary position in the cross section of the secondary particle and the aluminum content in the inside, not the interface of the primary particle, is measured, the aluminum content can be expressed as the same / similar / uniform regardless of the position of the primary particle, that is, whether the primary particle is close to the center or the surface of the secondary particle. In such a structure, even if cobalt is absent or present in only a very small amount, a stable layered structure can be maintained, no aluminum by-products or aluminum agglomerates are generated, and the capacity, efficiency, and life characteristics of the positive electrode active material can be improved simultaneously.
[0027] The lithium nickel-manganese composite oxide is specifically represented by the following chemical formula 1. [Chemical formula 1] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1
[0028] In Chemical Formula 1, 0.9≦a1≦1.8, 0.6≦x1≦0.8, 0.1≦y1≦0.4, 0≦z1≦0.03, 0≦w1≦0.3, 0.9≦x1+y1+z1+w1≦1.1, and 0≦b1≦0.1; M 1is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr, and X is one or more elements selected from F, P, and S.
[0029] In Chemical Formula 1, 0.9 ≦ a1 ≦ 1.5, or 0.9 ≦ a1 ≦ 1.2 may hold. Further, Chemical Formula 1 contains aluminum, and in this case, 0.6 ≦ x1 ≦ 0.8, 0.1 ≦ y1 ≦ 0.39, 0.01 ≦ z1 ≦ 0.03, and 0 ≦ w1 ≦ 0.29 can be satisfied. For example, 0.6 ≦ x1 ≦ 0.8, 0.1 ≦ y1 ≦ 0.39, 0.01 < z1 ≦ 0.03, and 0 ≦ w1 ≦ 0.29 can be satisfied.
[0030] In Chemical Formula 1, for example, 0.6 ≦ x1 ≦ 0.79, 0.6 ≦ x1 ≦ 0.78, 0.6 ≦ x1 ≦ 0.75, 0.65 ≦ x1 ≦ 0.8, or 0.7 ≦ x1 ≦ 0.79, 0.1 ≦ y1 ≦ 0.35, 0.1 ≦ y1 ≦ 0.30, 0.1 ≦ y1 ≦ 0.29, 0.15 ≦ y1 ≦ 0.39, or 0.2 ≦ y1 ≦ 0.3, 0.01 ≦ z1 ≦ 0.025, 0.01 < z1 ≦ 0.02, or 0.01 < z1 ≦ 0.019, 0 ≦ w1 ≦ 0.28, 0 ≦ w1 ≦ 0.27, 0 ≦ w1 ≦ 0.26, 0 ≦ w1 ≦ 0.25, 0 ≦ w1 ≦ 0.24, 0 ≦ w1 ≦ 0.23, 0 ≦ w1 ≦ 0.22, 0 ≦ w1 ≦ 0.21, 0 ≦ w1 ≦ 0.2, 0 ≦ w1 ≦ 0.15, 0 ≦ w1 ≦ 0.1, or 0 ≦ w1 ≦ 0.09 and the like may hold.
[0031] The lithium nickel - manganese - based composite oxide may be a cobalt - free compound that does not contain cobalt or contains a very small amount of cobalt. For example, the content of cobalt in the lithium nickel - manganese - based composite oxide may be 0 mol% to 0.01 mol% with respect to 100 mol% of the total metal excluding lithium.
[0032] The core particle may be in the form of a secondary particle formed by agglomeration of a plurality of primary particles. The secondary particles may be spherical, ellipsoidal, polyhedral, or irregular in shape, while the primary particles may be spherical, ellipsoidal, plate-like, or a combination thereof.
[0033] The core particles are susceptible to chemical attack by components in the electrolyte when the battery is operated under high voltage or high temperature conditions, and many side reactions with the electrolyte may occur, which may result in a large amount of gas generation and reduced battery life and safety. However, such problems can be solved by introducing a coating layer according to one embodiment described below.
[0034] Coating Layer In one embodiment, Al, Zr, and Mg are all contained in the coating layer, and compared to the case where any one of the three is omitted, the amount of gas generation under high voltage or high temperature driving conditions can be significantly reduced, and the life characteristics can be improved. 3+ , Zr 4+ , and Mg 2+ It can be said that it contains three kinds of metals or metal cations such as 2+, 3+, and 4+. By simultaneously coating three kinds of metal cations with oxidation numbers 2+, 3+, and 4+, the charge balance is increased, which can improve the high voltage characteristics.
[0035] The Al content in the coating layer is 0.1 mol% to 2 mol% relative to 100 mol% of the total metals excluding lithium in the positive electrode active material, and may be, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. This means only the content of aluminum contained in the coating layer apart from the aluminum contained in the core particles. The aluminum content in the coating layer can be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the aluminum content in the coating layer satisfies the above range, it is possible to form a coating layer with a uniform and thin thickness, the resistance of the positive electrode active material does not increase, side reactions with the electrolyte are effectively suppressed, and the life characteristics of the lithium secondary battery under high voltage and high temperature conditions can be improved. For example, if the aluminum content of the coating layer is too high, a uniform coating layer may not be formed or the resistance may increase, resulting in reduced charge / discharge efficiency and reduced life characteristics. Conversely, if the aluminum content of the coating layer is too low, a coating layer of appropriate thickness may not be formed, resulting in reduced effect of suppressing side reactions with the electrolyte.
[0036] The Zr content of the coating layer may be 0.1 mol% to 0.4 mol%, for example, 0.2 mol% to 0.4 mol%. The Mg content of the coating layer may be 0.1 mol% to 0.5 mol%, for example, 0.1 mol% to 0.4 mol%. When the coating contents of Zr and Mg satisfy the above ranges, the positive electrode active material forms a good coating layer without a decrease in capacity or an increase in resistance, and can effectively suppress side reactions with the electrolyte and effectively reduce the amount of gas generation under high voltage or high temperature conditions.
[0037] The ratio of Zr and Mg content to Al content in the coating layer is 0.06 to 0.65, for example, 0.1 to 0.6, 0.1 to 0.5, 0.1 to 0.45, 0.2 to 0.40, and may be more than 0.06 and less than 0.65, or more than 0.06 and less than 0.45. This means the content ratio of (Zr+Mg) / Al, and the content means the molar content. When the content ratio of each element in the coating layer satisfies the above range, the capacity characteristic and life characteristic at high voltage can be maximized.
[0038] According to an embodiment, the coating layer may be in the form of a film that continuously surrounds the surface of the core particle, for example, in the form of a shell that surrounds the entire surface of the core particle. This is different from a structure in which only a part of the surface of the core particle is partially coated. According to an embodiment, the coating layer may be formed in a form that entirely surrounds the surface of the core particle, but may be formed with a very thin and uniform thickness, so that the positive electrode active material does not increase in resistance or decrease in capacity, improves structural stability, effectively suppresses side reactions with the electrolyte, reduces the amount of gas generation under high voltage and high temperature conditions, and achieves long life characteristics.
[0039] The thickness of the coating layer is 5 nm to 500 nm, and may be, for example, 5 nm to 450 nm, 10 nm to 400 nm, 20 nm to 350 nm, 30 nm to 300 nm, 30 nm to 250 nm, 30 nm to 200 nm, 30 nm to 150 nm, 50 nm to 500 nm, 80 nm to 500 nm, or 100 nm to 500 nm. When the coating layer satisfies the above thickness range, the coating can improve the structural stability of the positive electrode active material and effectively suppress side reactions with the electrolyte, even if the resistance does not increase or the capacity does not decrease due to the coating. The thickness of the coating layer can be measured, for example, by TOF-SIMS, XPS, or EDS analysis, and the thickness range of the coating layer can be measured by TEM-EDS line profile.
[0040] According to an embodiment, the coating layer has a thickness of tens to hundreds of nanometers and is uniform. For example, the deviation of the coating layer thickness within one positive electrode active material particle may be 20% or less, 18% or less, or 15% or less. Here, the deviation of the coating layer thickness refers to the thickness of the coating layer within one positive electrode active material particle. The deviation of the coating layer thickness means, for example, that the thickness of 10 or more points is measured in an electron microscope image of a cross section of one positive electrode active material particle, the arithmetic average is calculated, and the absolute value of the difference between one data and the arithmetic average value is divided by the arithmetic average value and multiplied by 100. The deviation or standard deviation of the coating layer thickness satisfies the above range, which means that a coating layer of uniform thickness is well formed in the form of a film on the surface of the positive electrode active material particle, thereby improving the structural stability of the positive electrode active material, effectively suppressing side reactions with the electrolyte, and minimizing the increase in resistance and the decrease in capacity due to the coating.
[0041] Due to the characteristics of each element in the coating layer, Al exists in the form of a continuous film, while Zr and Mg exist in the form of islands.
[0042] In one embodiment, Al, Zr, and Mg may each form a separate layer. For example, the positive electrode active material according to one embodiment may include a first coating layer containing Al located on the surface of the core particle, and a second coating layer containing Zr and Mg located on the first coating layer. Aluminum is first attached or absorbed on the surface of the core particle to form a first coating layer in the form of a thin film, and zirconium and magnesium are coated thereon to form a second coating layer. Of course, Al, Zr, and Mg are mixed in the first and second coating layers, but the first coating layer can be said to be an Al-rich coating layer mainly composed of Al, and the second coating layer can be said to be a Zr / Mg-rich coating layer mainly composed of Zr and Mg.
[0043] The thickness of the first coating layer and the second coating layer is not particularly limited, but the thickness of the first coating layer is 1 nm to 200 nm, for example, 10 nm to 200 nm, 20 nm to 200 nm, or 30 nm to 180 nm. The thickness of the second coating layer is 2 nm to 300 nm, for example, 10 nm to 250 nm, 20 nm to 200 nm, 30 nm to 300 nm, or 50 nm to 300 nm. When each thickness satisfies the above range, the coating can improve the structural stability of the positive electrode active material without increasing the resistance or decreasing the capacity, and can effectively suppress side reactions with the electrolyte to effectively reduce the amount of gas generated during high voltage and high temperature operation.
[0044] Meanwhile, the coating layer may further include nickel, manganese, or a combination thereof in addition to Al, Zr, and Mg. Nickel and manganese are contained in the core particles and flow in during the coating layer formation process, and the content thereof is not particularly limited. The coating layer according to an embodiment necessarily contains Al, Zr, and Mg, and selectively contains nickel and manganese, so that it is formed to a thin and uniform thickness, and can improve the high voltage characteristics and life characteristics of the positive electrode active material.
[0045] Grain boundary coating part In the process of forming the coating layer, aluminum may be diffused into the core particles. Thus, the positive electrode active material according to an embodiment may further include a grain boundary coating portion containing aluminum located on the surface of the primary particle inside the secondary particle. Here, the secondary particle refers to the core particle, and the inside of the secondary particle refers to the entire inside except for the surface of the secondary particle, or may refer to a region from the surface of the secondary particle to about 60% of the radius in the direction toward the center of the secondary particle. The grain boundary coating portion is a concept distinct from the coating layer on the surface of the core particle, and refers to a coating portion formed on the surface of the primary particle located inside the core particle. The presence of the grain boundary coating portion can be confirmed by SEM-EDS analysis of the cross section of the positive electrode active material. By forming the aluminum grain boundary coating portion, the positive electrode active material is structurally more stabilized and the life characteristics are improved.
[0046] The aluminum content in the grain boundary coating portion is not particularly limited, and as an example, the aluminum content in the grain boundary coating portion may be less than the aluminum content in the coating layer.
[0047] The grain boundary coating portion may further include magnesium in addition to aluminum, and may further include nickel, manganese, or a combination thereof.
[0048] The average particle size (D 50 The average particle size is determined by measuring the size (diameter or major axis length) of 20 or more particles randomly in a scanning electron microscope image of the positive electrode active material to obtain a particle size distribution, and calculating the diameter (D) of the particle that occupies 50% of the cumulative volume in the particle size distribution. 50 When the average particle size of the positive electrode active material satisfies the above range, high capacity and long life can be achieved, and it is advantageous to form the coating layer according to an embodiment.
[0049] In the positive electrode active material according to an embodiment, the content of cobalt may be, for example, 0.01 mol % or less, 0.005 mol % or less, 0.001 mol % or less, for example, 0 mol % to 0.01 mol %, relative to 100 mol % of all metals excluding lithium. The positive electrode active material according to an embodiment may be, for example, a cobalt-free positive electrode active material.
[0050] In addition, the positive electrode active material according to an embodiment may be characterized in that it does not contain sodium. Although sodium ions can be generally used in a process for manufacturing a positive electrode active material, according to a manufacturing method described below, it is possible to form core particles with a stable structure and a coating layer with a uniform thickness without using sodium ions.
[0051] Method for producing positive electrode active material In one embodiment, a method for producing a positive electrode active material is provided, which includes: (i) mixing a nickel-manganese-based composite hydroxide having a nickel content of 60 mol % or more relative to 100 mol % of total metals and a lithium raw material, and performing a first heat treatment to obtain a lithium nickel-manganese-based composite oxide; (ii) introducing the obtained lithium nickel-manganese-based composite oxide into a solution in which an Al raw material is mixed in an aqueous solvent, mixing, and then drying; and (iii) dry-mixing the obtained product with a Zr raw material and an Mg raw material, and performing a second heat treatment to obtain a positive electrode active material.
[0052] The nickel-manganese composite hydroxide may contain no cobalt or may contain a very small amount of cobalt, for example, a cobalt-free nickel-manganese composite hydroxide, for example, a cobalt-free nickel-manganese-aluminum composite hydroxide. The nickel-manganese composite hydroxide may be produced by a general coprecipitation method.
[0053] The nickel content in the nickel-manganese composite hydroxide is 60 mol% or more relative to 100 mol% of the total metal, and can be, for example, 60 mol% to 80 mol%, 65 mol% to 80 mol%, 70 mol% to 80 mol%, 60 mol% to 79 mol%, 60 mol% to 78 mol%, or 60 mol% to 75 mol%, etc. When the nickel content satisfies the above range, a high capacity can be achieved, and structural safety can be improved even if the cobalt content is reduced.
[0054] The manganese content in the nickel-manganese composite hydroxide may be 10 mol% to 40 mol%, 10 mol% to 39 mol%, 10 mol% to 35 mol%, 10 mol% to 30 mol%, 10 mol% to 29 mol%, 15 mol% to 39 mol%, 20 mol% to 39 mol%, 20 mol% to 30%, etc., relative to 100 mol% of the total metal.
[0055] In addition, when the nickel-manganese composite hydroxide further contains aluminum, the content of aluminum is 0.1 mol% or more, 0.5 mol% or more, or 1 mol% or more, for example, 1 mol% to 3 mol%, 1 mol% to 2.5 mol%, 1 mol% to 2 mol%, or 1 mol% to 1.9 mol%, based on 100 mol% of the total metal. When the manganese and aluminum contents in the composite hydroxide satisfy the above ranges, the structural safety of the positive electrode active material can be improved while realizing a high capacity, and the production cost can be reduced to improve the economic efficiency.
[0056] In the nickel-manganese composite hydroxide, the cobalt content may be 0.01 mol% or less, 0.005 mol% or less, or 0.001 mol% or less, based on 100 mol% of the total metal. Such nickel-manganese composite hydroxide can avoid the increase in unit price due to cobalt, making it economical, maximizing capacity, and improving structural stability.
[0057] An example of the nickel-manganese composite hydroxide is represented by the following chemical formula 2. [Chemical formula 2] Ni x2 Mn y2Al z2 M 2 w2 (OH)2
[0058] In the chemical formula 2, 0.6≦x2≦0.8, 0.1≦y2≦0.4, 0≦z2≦0.03, 0≦w2≦0.3, and 0.9≦x2+y2+z2+w2≦1.1; M 2 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr.
[0059] In Chemical Formula 2, for example, 0.6≦x2≦0.8, 0.1≦y2≦0.39, 0.01≦z2≦0.03, and 0≦w2≦0.29.
[0060] The nickel-manganese composite hydroxide is in the form of particles, and the average particle size (D 50 ) can be 10 μm to 18 μm, 11 μm to 16 μm, or 12 μm to 15 μm.
[0061] By using aluminum as a raw material in the preparation of the precursor without further doping aluminum in the core particle preparation process, a nickel-manganese-aluminum composite hydroxide in which aluminum is uniformly dispersed within the structure can be used as the precursor. By using such a precursor, a positive electrode active material can be produced that does not contain cobalt and that stably maintains a layered structure even after repeated charging and discharging, and aluminum by-products and aluminum aggregates are not formed, thereby improving the capacity, efficiency characteristics, and life characteristics of the positive electrode active material.
[0062] The nickel-manganese composite hydroxide and the lithium raw material can be mixed in a molar ratio of 1:0.9 to 1:1.8, for example, 1:0.9 to 1:1.5 or 1:0.9 to 1:1.2. The first heat treatment can be performed in an oxygen atmosphere, for example, at a temperature range of 750°C to 950°C, or 780°C to 900°C, or 810°C to 890°C, for 2 hours to 20 hours, or 4 hours to 12 hours. A lithium nickel-manganese composite oxide can be obtained by the heat treatment. The obtained composite oxide contains nickel at 60 mol% or more, for example, 60 mol% to 80 mol%, based on 100 mol% of the total metal, and does not contain cobalt or contains a very small amount of cobalt of 0.01 mol% or less.
[0063] Lithium nickel-manganese composite oxide has a significantly different content of residual lithium on the particle surface from existing nickel-based oxides of other compositions, such as lithium nickel-cobalt-manganese composite oxide and lithium nickel-cobalt-aluminum composite oxide, and has many different surface properties, making it impossible to form a good coating layer with a uniform film shape using existing coating methods. In one embodiment, a method is provided for improving high voltage characteristics by forming a uniform coating layer with a very thin thickness on the surface of lithium nickel-manganese composite oxide with a very small cobalt content and a nickel content of 60 mol% or more.
[0064] In one embodiment, the lithium nickel-manganese composite oxide obtained by the first heat treatment is mixed with an aqueous solvent containing an aluminum raw material, and then dried and subjected to a second heat treatment to perform an AI coating by a kind of wet method.
[0065] The aqueous solvent may include distilled water, an alcohol-based solvent, or a combination thereof. The aluminum raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof. As an example, the aluminum raw material may include aluminum sulfate, which is advantageous in forming a coating layer having a uniform thickness on the surface of the lithium nickel-manganese composite oxide particles.
[0066] The aluminum raw material is a raw material for forming the coating layer, and the aluminum content in the aluminum raw material can be designed to be 0.1 mol% to 2 mol% with respect to 100 mol% of the total metals excluding lithium in the finally obtained positive electrode active material, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. By designing the content of the AI coating within the above ranges, a coating layer having a thin thickness of tens to hundreds of nanometers and a uniform thickness can be formed, and the amount of gas generation of the lithium secondary battery under high voltage or high temperature driving conditions can be reduced, and high capacity and long life characteristics can be improved.
[0067] The solution in which the aluminum raw material is mixed with the aqueous solvent has a pH of 1.5 to 3.5, for example, 2.0 to 3.4, 2.5 to 3.3, 2.7 to 3.3, or 2.9 to 3.2. The lithium nickel-manganese composite oxide can be added to the aqueous solvent in which the aluminum raw material is mixed and mixed for about 5 to 80 minutes, or 5 to 60 minutes, or 5 to 40 minutes. The mixed solution after stirring has a pH of 4.5 to 8.5, for example, 5.0 to 8.0, 5.5 to 7.5, or 6.0 to 7.0. When such conditions are satisfied, it is advantageous for a coating layer of uniform thickness to be formed.
[0068] Drying after the mixing step can be understood as a step of removing the solvent, and can be carried out at, for example, 40°C to 240°C, 100°C to 220°C, or 150°C to 200°C.
[0069] The second heat treatment can be understood as a process for forming an Al / Zr / Mg coating layer, and can be carried out, for example, in an oxygen atmosphere at a temperature range of 700°C to 850°C, 750°C to 840°C, or 800°C to 830°C for 2 hours to 20 hours, or 3 hours to 10 hours. The second heat treatment temperature can be lower than the first heat treatment temperature, and the second heat treatment time is preferably the same as or shorter than the first heat treatment time. By carrying out the second heat treatment under such conditions, a desired coating layer can be obtained.
[0070] The Zr content in the Zr raw material can be designed to be 0.1 mol % to 0.4 mol %, or 0.2 mol % to 0.4 mol %, based on 100 mol % of all metals excluding lithium in the positive electrode active material, and the Mg content in the Mg raw material can be designed to be 0.1 mol % to 0.5 mol %, or 0.1 mol % to 0.4 mol %, based on 100 mol % of all metals excluding lithium in the positive electrode active material.
[0071] The Zr source can include, for example, zirconium oxide, zirconium silicate, or a combination thereof. The Mg source can include, for example, magnesium oxide, magnesium phosphate, magnesium carbonate, or a combination thereof.
[0072] positive electrode In one embodiment, a positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material described above. The positive electrode active material layer may further include other types of positive electrode active materials in addition to the positive electrode active materials described above. The positive electrode active material layer may also optionally include a binder, a conductive material, or a combination thereof.
[0073] According to one embodiment, the loading level of the positive electrode active material layer is 5 mg / cm 2 ~40mg / cm 2 For example, 5 mg / cm 2 ~30mg / cm2 or 10 mg / cm 2 ~20mg / cm 2 or 10±5mg / cm 2 In addition, the density of the positive electrode active material layer in the final rolled positive electrode may be 3.3 g / cc to 3.7 g / cc, for example, 3.3 g / cc to 3.6 g / cc or 3.4 g / cc to 3.58 g / cc. When the positive electrode active material according to an embodiment is applied, it is advantageous to achieve such a loading level and positive electrode density, and a positive electrode satisfying the above-mentioned ranges of loading level and positive electrode density is suitable for realizing a lithium secondary battery with high capacity and high energy density.
[0074] binder The binder serves to make the positive electrode active material particles adhere well to each other and to make the positive electrode active material adhere well to the current collector. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, nylon, etc.
[0075] Conductive material The conductive material is used to impart electrical conductivity to the electrodes, and any material that does not cause a chemical change in the battery that is constructed and is electronically conductive can be used. Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metal-based materials containing copper, nickel, aluminum, silver, and the like in the form of metal powder or metal fibers; conductive polymers such as polyphenylene derivatives; and mixtures thereof.
[0076] The content of the binder and the conductive material may be 0.5% by weight to 5% by weight, respectively, relative to 100% by weight of the positive electrode active material layer.
[0077] The positive electrode current collector can be made of Al, but is not limited to this.
[0078] Lithium secondary battery In one embodiment, a lithium secondary battery is provided that includes the positive electrode, the negative electrode, and the electrolyte described above.
[0079] Lithium secondary batteries can be classified into cylindrical, square, pouch, coin, etc. types according to their shapes. FIG. 1 is a schematic diagram showing a lithium secondary battery according to an embodiment. Referring to FIG. 1, a lithium secondary battery 100 may include an electrode assembly 40 having a separator 30 between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is housed. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown).
[0080] The lithium secondary battery according to an embodiment may be capable of being charged at a high voltage or may be suitable for being driven at a high voltage. For example, the charging voltage of the lithium secondary battery may be 4.45 V or more, such as 4.45 V to 4.7 V, 4.45 V to 4.6 V, or 4.45 V to 4.55 V. By applying the positive electrode active material according to an embodiment, the lithium secondary battery can significantly reduce the amount of gas generated even when charged at a high voltage, and can achieve high capacity and long life characteristics.
[0081] negative electrode The negative electrode can include a current collector and a negative electrode active material layer located on the current collector, the negative electrode active material layer including a negative electrode active material and can further include a binder, a conductive material, or a combination thereof.
[0082] negative electrode active material The negative electrode active material includes a material capable of reversibly inserting / desorbing lithium ions, lithium metal, an alloy of lithium metal, a material dopable and dedopable with lithium, or a transition metal oxide.
[0083] Examples of the material capable of reversibly inserting / desorbing the lithium ions include carbon-based negative electrode active materials, which can include, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flaky, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, fired coke, and the like.
[0084] As the alloy of the lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn can be used.
[0085] As the material dopable and dedopable with lithium, an Si-based negative electrode active material or an Sn-based negative electrode active material can be used. The Si-based negative electrode active material can be silicon, a silicon-carbon composite, SiOx (0 < x < 2), an Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, for example, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof), or a combination thereof. The Sn-based negative electrode active material can be Sn, SnO2, an Sn alloy, or a combination thereof.
[0086] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle size (D 50 ) may be, for example, 0.5 μm to 20 μm. According to one embodiment, the silicon-carbon composite may be in the form of silicon particles and the surfaces of the silicon particles coated with amorphous carbon. For example, it may include secondary particles (cores) formed by granulating primary silicon particles, and an amorphous carbon coating layer (shell) located on the surfaces of the secondary particles. The amorphous carbon may also be located between the primary silicon particles, for example, the primary silicon particles may be coated with amorphous carbon. The secondary particles may be present dispersed in an amorphous carbon matrix.
[0087] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core including crystalline carbon and silicon particles, and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include soft or hard carbon, mesophase pitch carbide, calcined coke, etc.
[0088] When the silicon-carbon composite contains silicon and amorphous carbon, the silicon content may be 10% to 50% by weight and the amorphous carbon content may be 50% to 90% by weight, relative to 100% by weight of the silicon-carbon composite. When the composite contains silicon, amorphous carbon and crystalline carbon, the silicon content may be 10% to 50% by weight, the crystalline carbon content may be 10% to 70% by weight, and the amorphous carbon content may be 20% to 40% by weight, relative to 100% by weight of the silicon-carbon composite.
[0089] The thickness of the amorphous carbon coating layer may be 5 nm to 100 nm. 50) can be 10 nm to 1 μm, or 10 nm to 200 nm. The silicon particles may exist alone as silicon, or in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon can be represented by SiO x (0 < x < 2). At this time, the atomic content ratio of Si:O indicating the degree of oxidation can be 99:1 to 33:67. In this specification, unless otherwise defined, the average particle size (D 50 ) means the diameter of the particle with a cumulative volume of 50% by volume in the particle size distribution.
[0090] The Si-based negative electrode active material or the Sn-based negative electrode active material can be used by mixing with a carbon-based negative electrode active material. When the Si-based negative electrode active material or the Sn-based negative electrode active material and the carbon-based negative electrode active material are used in combination, the mixing ratio can be 1:99 to 90:10 by weight.
[0091] binder The binder serves to make the negative electrode active material particles adhere well to each other and make the negative electrode active material adhere well to the current collector. As the binder, a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof can be used.
[0092] Examples of the non-aqueous binder include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.
[0093] The water-based binder may be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.
[0094] When an aqueous binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. As the cellulose-based compound, one or more of carboxymethylcellulose, hydroxypropylmethylcellulose, methylcellulose, or alkali metal salts thereof may be mixed and used. As the alkali metal, Na, K, or Li may be used.
[0095] The dry binder can be a fiberizable polymeric material such as polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.
[0096] Conductive material The conductive material is used to impart electrical conductivity to the electrodes, and may be any material that does not cause chemical changes in the battery and is electronically conductive. Specific examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metal-based materials in the form of metal powder or metal fibers, including copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and mixtures thereof.
[0097] The content of the negative electrode active material may be 95% to 99.5% by weight relative to 100% by weight of the negative electrode active material layer, and the content of the binder may be 0.5% to 5% by weight relative to 100% by weight of the negative electrode active material layer. For example, the negative electrode active material layer may contain 90% to 99% by weight of the negative electrode active material, 0.5% to 5% by weight of the binder, and 0.5% to 5% by weight of the conductive material.
[0098] Current collector The negative electrode current collector can include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or alloys thereof, and can be in foil, sheet, or foam form. The thickness of the negative electrode current collector can be, for example, 1 μm to 20 μm, 5 μm to 15 μm, or 7 μm to 10 μm.
[0099] electrolyte The electrolyte for a lithium secondary battery can be, by way of example, an electrolytic solution, which can include a non-aqueous organic solvent and a lithium salt.
[0100] The non-aqueous organic solvent serves as a medium through which the ions involved in the electrochemical reactions of the battery can migrate. The non-aqueous organic solvent may be a carbonate-, ester-, ether-, ketone-, or alcohol-based solvent, an aprotic solvent, or a combination thereof.
[0101] Examples of the carbonate solvent include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanolide, mevalonolactone, valerolactone, caprolactone, etc. Examples of the ether solvent include dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, and tetrahydrofuran. Examples of the ketone solvent include cyclohexanone. Examples of the alcohol solvent include ethyl alcohol and isopropyl alcohol. Examples of the aprotic solvent include nitriles such as R-CN (R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms, and may contain a double bond, an aromatic ring, or an ether group); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane and 1,4-dioxolane; and sulfolanes.
[0102] The non-aqueous organic solvent may be used alone or in combination of two or more kinds. When using in combination of two or more kinds, the mixing ratio may be appropriately adjusted according to the desired battery performance, which is widely understood by those working in the field.
[0103] When a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate can be mixed and used, and the cyclic carbonate and the chain carbonate can be mixed in a volume ratio of 1:1 to 1:9.
[0104] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, the carbonate solvent and the aromatic hydrocarbon organic solvent may be mixed in a volume ratio of 1:1 to 30:1.
[0105] The electrolyte may further contain a vinyl ethyl carbonate, vinylene carbonate or ethylene carbonate based compound to improve the battery life.
[0106] Representative examples of the ethylene carbonate-based compounds include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0107] Lithium salts are substances that dissolve in organic solvents and act as a source of lithium ions in the battery to enable basic lithium secondary battery operation and facilitate the movement of lithium ions between the positive and negative electrodes. Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).
[0108] The lithium salt is preferably used at a concentration within the range of 0.1 M to 2.0 M. If the lithium salt concentration is within the above range, the electrolyte has appropriate ion conductivity and viscosity, and therefore can exhibit excellent performance and allow lithium ions to migrate effectively.
[0109] Separator Depending on the type of lithium secondary battery, a separator may be present between the positive electrode and the negative electrode. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer film of two or more layers of these may be used, and it is of course possible to use a mixed multilayer film such as a two-layer separator of polyethylene / polypropylene, a three-layer separator of polyethylene / polypropylene / polyethylene, or a three-layer separator of polypropylene / polyethylene / polypropylene.
[0110] The separator may include a porous substrate and a coating layer including an organic material, an inorganic material, or a combination thereof located on one or both sides of the porous substrate.
[0111] The porous substrate may be a polymer membrane formed of any one polymer selected from polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyether ketone, polyaryl ether ketone, polyetherimide, polyamide imide, polybenzimidazole, polyethersulfone, polyphenylene oxide, cyclic olefin copolymer, polyphenylene sulfide, polyethylene naphthalate, glass fiber, Teflon (registered trademark), and polytetrafluoroethylene, or a copolymer or mixture of two or more of these polymers.
[0112] The porous substrate can have a thickness of about 1 μm to 40 μm, for example, 1 μm to 30 μm, 1 μm to 20 μm, 5 μm to 15 μm, or 10 μm to 15 μm.
[0113] The organic material may include a (meth)acrylic copolymer including a first structural unit derived from (meth)acrylamide, a structural unit derived from (meth)acrylic acid or a (meth)acrylate, and a second structural unit including at least one of a structural unit derived from (meth)acrylamidosulfonic acid or a salt thereof.
[0114] The inorganic material may include, but is not limited to, inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof. The average particle size (D 50 ) may be 1 nm to 2000 nm, for example, 100 nm to 1000 nm, or 100 nm to 700 nm.
[0115] The organic material and the inorganic material may be mixed in one coating layer, or may be stacked in a coating layer including an organic material and a coating layer including an inorganic material.
[0116] The thickness of each of the coating layers may be from 0.5 μm to 20 μm, for example, from 1 μm to 10 μm, or from 1 μm to 5 μm.
[0117] Examples of the present invention and comparative examples are described below. The following examples are merely illustrative of the present invention, and the present invention is not limited to the following examples.
[0118] Example 1 1. Manufacturing of positive electrode active material Ni 0.75 Mn 0.23 Al 0.02 (OH)2 and LiOH were mixed in a molar ratio of 1:1.05 and subjected to a first heat treatment at 850°C for 8 hours in an oxygen atmosphere to obtain a composition of Li 1.05 Ni 0.75 Mn0.23 Al 0.02 O2 and the average particle size (D 50 A composite oxide in the form of secondary particles having a particle size of about 14 μm was produced.
[0119] After mixing aluminum sulfate with a distilled water solvent, the composite oxide prepared was added thereto and mixed for about 20 to 60 minutes. At this time, the aluminum content of the aluminum sulfate was designed to be 1.0 mol% relative to 100% by weight of the total metal excluding lithium in the final positive electrode active material, and mixed. After removing the solvent from the mixed solution and drying at 190°C, the resulting material was dry-mixed with zirconium oxide powder and magnesium oxide powder, and subjected to a second heat treatment at 825°C for 8 hours in an oxygen atmosphere to prepare the final positive electrode active material. The zirconium content of the zirconium oxide was designed to be 0.2 mol% relative to 100% by weight of the total metal excluding lithium in the final positive electrode active material, and the magnesium content of the magnesium oxide was designed to be 0.1 mol% relative to 100% by weight of the total metal excluding lithium in the final positive electrode active material, and mixed.
[0120] 2. Manufacturing of lithium secondary batteries 98.5 wt% of the prepared positive electrode active material, 1.0 wt% of polyvinylidene fluoride binder, and 0.5 wt% of carbon nanotube conductive material were mixed to prepare a positive electrode active material layer slurry, which was then coated on an aluminum foil current collector, dried, and rolled to prepare a positive electrode. At this time, the loading level of the positive electrode active material layer was 10 mg / cm. 2 and the density of the final rolled cathode was about 3.4 g / cc.
[0121] A negative electrode active material layer slurry was prepared by mixing 97.5 wt% graphite negative electrode active material, 1.5 wt% carboxymethyl cellulose, and 1 wt% styrene butadiene rubber in an aqueous solvent. The negative electrode active material layer slurry was coated on a copper foil current collector, and then dried and rolled to prepare a negative electrode.
[0122] A polytetrafluoroethylene separator was used, and a lithium secondary battery was manufactured in a conventional manner using an electrolyte solution in which 1M LiPF6 was dissolved in a solvent in which ethylene carbonate and dimethyl carbonate were mixed in a volume ratio of 3:7.
[0123] Example 2 In the preparation of the positive electrode active material, the magnesium content of the magnesium oxide was designed and mixed to be 0.2 mol % based on 100 wt % of the total metals excluding lithium in the final positive electrode active material, but the positive electrode active material and the lithium secondary battery were prepared in substantially the same manner as in Example 1.
[0124] Example 3 A positive electrode active material and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that in the preparation of the positive electrode active material, the magnesium content of the magnesium oxide was designed and mixed to be 0.4 mol % based on 100 wt % of the total metals excluding lithium in the final positive electrode active material.
[0125] Example 4 A positive electrode active material and a lithium secondary battery were manufactured in substantially the same manner as in Example 2, except that in the preparation of the positive electrode active material, the content of zirconium in the zirconium oxide was designed and mixed to be 0.4 mol % based on 100 wt % of the total metals excluding lithium in the final positive electrode active material.
[0126] Comparative Example 1 A positive electrode active material and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that magnesium oxide powder was not added and Mg was not coated in the preparation of the positive electrode active material.
[0127] Comparative Example 2 A positive electrode active material was prepared in a manner substantially similar to that of Example 1, except that the aluminum coating was performed in a dry manner, and Zr and Mg were not coated. 1.05 Ni 0.75Mn 0.23 Al 0.02 A composite oxide in the form of secondary particles, O2, and aluminum oxide powder were mixed and heat-treated in an oxygen atmosphere at 825°C for 8 hours to prepare an Al-coated cathode active material in a dry manner. A lithium secondary battery was prepared in substantially the same manner as in Example 1, except that the cathode active material was used.
[0128] Comparative Example 3 Ni 0.75 Mn 0.25 (OH)2, LiOH and Al2O3 were mixed in a molar ratio of 1:1:0.02 and heat-treated at 850℃ for 8 hours in an oxygen atmosphere to obtain a powder with an average particle size (D 50 An aluminum-doped composite oxide in the form of secondary particles having a particle size of about 14 μm was prepared. The aluminum-doped composite oxide thus prepared was mixed with aluminum oxide powder and heat-treated at 825° C. for 8 hours in an oxygen atmosphere to prepare an aluminum-coated cathode active material in a dry manner. A lithium secondary battery was prepared in substantially the same manner as in Example 1, except that this was used as the cathode active material.
[0129] Comparative Example 4 Ni 0.75 Mn 0.25 (OH)2, LiOH and Al2O3 were mixed in a molar ratio of 1:1:0.02 and heat-treated at 850℃ for 8 hours in an oxygen atmosphere to obtain a powder with an average particle size (D 50 A lithium secondary battery was manufactured in substantially the same manner as in Example 1, except that the aluminum doped composite oxide was used as a positive electrode active material.
[0130] Comparative Example 5 Ni 0.75 Mn 0.25 (OH)2 and LiOH were mixed in a 1:1 molar ratio and heat-treated in an oxygen atmosphere at 850°C for 8 hours to obtain a composition of LiNi 0.75 Mn 0.25 O2 and the average particle size (D 50A composite oxide having a secondary particle shape with a particle size of about 14 μm was prepared. A lithium secondary battery was prepared in substantially the same manner as in Example 1, except that the composite oxide was used as a positive electrode active material.
[0131] For ease of understanding, the design details of the positive electrode active materials of the examples and comparative examples are simply shown in Table 1 below.
[0132] [Table 1]
[0133] Evaluation example 1: Evaluation of initial charge / discharge capacity and efficiency The lithium secondary batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were initially charged and discharged at a constant current of 0.2 C to 4.45 V and a constant voltage of 0.05 C at 25° C., and then discharged at 0.2 C to a cut-off voltage of 3.0 V. Table 1 shows the initial charge capacity, initial discharge capacity, and the ratio of the latter to the former, which were efficiently calculated.
[0134] Evaluation example 2: Life characteristics Following the initial charge and discharge of Evaluation Example 1, a cycle of charging at 1.0 C and discharging at 1.0 C in the voltage range of 3.0 V to 4.45 V was repeated 25 or more times, and the ratio of the 25-cycle discharge capacity to the initial discharge capacity was calculated. Table 1 shows the ratio.
[0135] Evaluation example 3: Evaluation of gas generation rate The batteries of Example 2 and Comparative Examples 1 to 5 were initially charged to 4.45 V as in Evaluation Example 1, and then stored at 90° C. for 4 hours, after which the amount of gas generated in the batteries was measured. The results are shown in Table 1.
[0136] Referring to Table 1, in the case of Examples 1 to 4, the initial charge / discharge capacity and efficiency under high voltage conditions were maintained at a high level, the life characteristics were improved, and the amount of gas generation under high temperature conditions was significantly reduced.
[0137] In the case of Comparative Example 1 in which Mg coating was omitted, the life characteristics at high voltage were somewhat decreased, and the amount of gas generation at high temperature was higher than that of the Example. In the case of Comparative Example 2 in which Zr and Mg coating was omitted and Al was dry-coated, the life characteristics at high voltage were significantly decreased, and the amount of gas generation at high temperature was higher than that of the Example. In the case of Comparative Example 3 in which Al was separately doped during the synthesis of the core particles, Zr and Mg coating was omitted, and Al was dry-coated, the initial discharge capacity and charge / discharge efficiency at high voltage were decreased, the life characteristics were significantly low, and the amount of gas generation at high temperature was high. In the case of Comparative Example 4 in which Al was separately doped during the synthesis of the core particles and Al, Zr, and Mg coating were omitted, the life characteristics at high voltage were decreased, and the amount of gas generation at high temperature was significantly high. In the case of Comparative Example 5 in which Al was not introduced into the core particles and Al, Zr, and Mg coating were omitted, the life characteristics at high voltage were significantly decreased, and the amount of gas generation at high temperature was too high, which was not commercially viable.
[0138] Although the preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concepts defined in the claims also fall within the scope of the present invention. [Explanation of symbols]
[0139] 100 Lithium secondary battery 10 positive electrode 20 negative electrode 30 Separator 40 Electrode assembly 50 cases
Claims
1. Core particles containing a lithium nickel-manganese composite oxide having a nickel content of 60 mol % or more relative to 100 mol % of all metals excluding lithium; and The positive electrode active material includes a coating layer located on a surface of the core particle and containing Al, Zr, and Mg.
2. 2. The positive electrode active material according to claim 1, wherein the coating layer has an Al content of 0.1 mol% to 2 mol%, a Zr content of 0.1 mol% to 0.4 mol%, and a Mg content of 0.1 mol% to 0.5 mol%, relative to 100 mol% of all metals excluding lithium.
3. 2. The positive electrode active material according to claim 1, wherein the ratio of Zr and Mg to Al in the coating layer is 0.1 to 0.
65.
4. The positive electrode active material according to claim 1 , wherein the coating layer is in the form of a shell that continuously surrounds the surface of the core particle.
5. The positive electrode active material according to claim 1 , wherein the coating layer has a thickness of 5 nm to 500 nm.
6. 10. The positive electrode active material of claim 1, wherein the coating layer further comprises nickel, manganese, or a combination thereof.
7. 2. The positive electrode active material according to claim 1, wherein the lithium nickel-manganese composite oxide of the core particle has a nickel content of 60 mol % to 80 mol % relative to 100 mol % of all metals excluding lithium.
8. The lithium nickel-manganese composite oxide of the core particle is a lithium nickel-manganese-aluminum composite oxide further containing aluminum in addition to nickel and manganese, 2. The positive electrode active material according to claim 1, wherein the lithium nickel-manganese-aluminum composite oxide has an aluminum content of 1 mol % to 3 mol % relative to 100 mol % of all metals excluding lithium.
9. The positive electrode active material according to claim 1, wherein the lithium nickel-manganese composite oxide of the core particle is represented by the following chemical formula 1: [Chemical formula 1] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1 In Chemical Formula 1, 0.9≦a1≦1.8, 0.6≦x1≦0.8, 0.1≦y1≦0.4, 0≦z1≦0.03, 0≦w1≦0.3, 0.9≦x1+y1+z1+w1≦1.1, and 0≦b1≦0.1; M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr, and X is one or more elements selected from F, P, and S.
10. 10. The positive electrode active material according to claim 9, wherein in Chemical Formula 1, 0.6≦x1≦0.8, 0.1≦y1≦0.39, 0.01≦z1≦0.03, and 0≦w1≦0.29 are satisfied.
11. 2. The positive electrode active material according to claim 1, wherein the content of cobalt is 0 mol % to 0.01 mol % relative to 100 mol % of all metals excluding lithium.
12. The positive electrode active material according to claim 1 , wherein the core particle is in the form of a secondary particle formed by agglomeration of a plurality of primary particles.
13. The positive electrode active material of claim 12 , further comprising a grain boundary coating portion containing Al and located on a surface of a primary particle inside the secondary particle.
14. The positive electrode active material according to claim 13 , wherein the Al content in the grain boundary coating portion is less than the Al content in the coating layer.
15. The positive electrode active material according to claim 13 , wherein the grain boundary coating portion further contains Mg.
16. The average particle size (D 50 2. The positive electrode active material according to claim 1, wherein the average particle diameter is 10 μm to 18 μm.
17. 10. The cathode active material of claim 1, wherein the cathode active material is free of sodium.
18. A nickel-manganese composite hydroxide having a nickel content of 60 mol % or more relative to 100 mol % of the total metals and a lithium raw material are mixed and subjected to a first heat treatment to obtain a lithium nickel-manganese composite oxide; The obtained lithium nickel-manganese composite oxide is put into a solution in which an Al raw material is mixed in an aqueous solvent, mixed, and then dried. the resulting mixture is dry-mixed with a Zr raw material and a Mg raw material, and the mixture is subjected to a second heat treatment to obtain a positive electrode active material.
19. The Al content in the Al raw material is 0.1 mol % to 2 mol % relative to 100 mol % of all metals excluding lithium in the positive electrode active material, The Zr content in the Zr raw material is 0.1 mol % to 0.4 mol % relative to 100 mol % of all metals excluding lithium in the positive electrode active material, The method for producing a positive electrode active material according to claim 18, wherein the Mg content in the Mg raw material is 0.1 mol % to 0.5 mol % relative to 100 mol % of all metals excluding lithium in the positive electrode active material.
20. The Al source includes aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof; The Zr source comprises zirconium oxide, zirconium silicate, or a combination thereof; 20. The method for producing a positive electrode active material according to claim 18, wherein the Mg raw material comprises magnesium oxide, magnesium phosphate, magnesium carbonate, or a combination thereof.
21. The method for producing a positive electrode active material according to claim 18, wherein the solution in which the aluminum raw material is mixed in the aqueous solvent has a pH of 1.5 to 3.
5.
22. The first heat treatment is carried out at 750°C to 950°C, The method for producing a positive electrode active material according to claim 18, wherein the second heat treatment is performed at 700°C to 850°C.
23. The nickel-manganese-based composite hydroxide is a nickel-manganese-aluminum-based composite hydroxide further containing aluminum, and the content of aluminum in the lithium nickel-manganese-aluminum-based composite hydroxide is 1 mol % to 3 mol % relative to 100 mol % of the total metal. The method for producing a positive electrode active material according to claim 18.
24. A positive electrode current collector, and a positive electrode active material layer located on the positive electrode current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 23.
25. The positive electrode according to claim 24 . a negative electrode, and A lithium secondary battery comprising an electrolyte.
26. 26. The lithium secondary battery according to claim 25, having a charging voltage of 4.45 V or more.
Citation Information
Patent Citations
Li-Ni COMPOSITE OXIDE PARTICLE POWDER FOR NONAQUEOUS ELECTROLYTE SECONDARY BATTERY, ITS MANUFACTURING METHOD, AND NONAQUEOUS ELECTROLYTE SECONDARY BATTERY
JP2010092848A
Composite cobalt-free positive electrode material and preparation method therefor
WO2021238202A1